A study of an operative outcome of a basitrochanteric fractures of the hip treated by dynamic hip screw and enders nail with percutaneous canulated cancellous screw - Vyas, Ambrish J.; Patel, Vijay J.; Patel, Keval H.; Panchal, Ravi G. (International Journal of Research in Orthopaedics, 2019)
Background: Basicervical or cervicotrochanteric fracture of the femur is considered stable variety of fracture pattern. Most common incidence is seen in elderly patient and in young patient with probably high energy trauma. Appropriate Osteosynthesis confers excellent outcome when reduction is optimally achieved. Methods: 86 basitrochanteric fractures had been treated with enders nail or dynamic hip screw (DHS) at our institute by a single surgeon. Implant selection was done purely based on plain radiograph, associated co-morbidities and fracture geometry. Patients had been followed up at 1 month, 3 month and 6 month. Results: In our study there were 86 patients out of which 63 patients (73.25%) were treated with enders nail and 23 patients (26.74%) were treated with DHS. Mean age of patients was 57 years. We noted minimum follow up of 8 months while maximum follow up of 4.5 years where as mean follow up duration is 18 months. We almost noted excellent to fair results in both groups. Conclusions: Most of the implants in basitrochanteric fractures worked on control collapse principle. Both DHS and enders nail with percutaneous cc screw follow this principle and when used with a proper technique, optimal reduction usually fetch the favourable outcomes with minimalistic approach.